Cover Feature: Furanosyl Oxocarbenium Ion Conformational Energy Landscape Maps as a Tool to Study the Glycosylation Stereoselectivity of 2‐Azidofuranoses, 2‐Fluorofuranoses and Methyl Furanosyl Uronates (Chem. Eur. J. 29/2019). Issue 29 (17th April 2019) - van der Vorm, Stefan; Hansen, Thomas; van Rijssel, Erwin R.; Dekkers, Rolf; Madern, Jerre M.; Overkleeft, Herman S.; Filippov, Dmitri V.; van der Marel, Gijsbert A.; Codée, Jeroen D. C.
Abstract : Energy maps of the full conformational space of 5‐membered ring glycosyl oxocarbenium ions have been generated to probe the stereoelectronic effects of C‐2‐fluoride, C‐2‐azide and C‐4‐carboxylic acid ester substituents. The computational results describing the overall shape of the reactive intermediates were complemented by experiments to show that the vast majority of studied furanosides react in an 1, 2‐ cis selective manner in SN 1‐type glycosylation reactions. More information can be found in the Full Paper by J. D. C. Codée et al. on page 7149 .